Statistical Study on the Linkage of Child (Under-5) Mortality and Bio-Demographic Variables - Singh, G. P.; Tripathi, A.; Singh, S. K.; Singh, Umesh (Journal of Informatics and Mathematical Sciences, 2015)
In this study we tried to find out the factors which are effecting the child mortality in state Uttar Pradesh and importance of such factors into predicting child mortality. For this study, the latest births by ‘ever married women' of Uttar Pradesh were considered from District Level Household and Facility Survey (DLHS-3) data. Factors were checked for association with child mortality by using of chi-square test. Further logistic regression analysis applied to find out adjusted effect of each factor. For checking the predictive capability of logistic regression model we applied statistic. It was found Wealth index quintile, type of birth, mother's age at time of birth, and father's education were significant effect to child mortality. The value is (2.3%).